Gaya Resolusi Konflik Mahasiswa dengan Pola Asuh Otoriter dan Dampaknya terhadap Kesejahteraan Psikologis - Bunga Febrian Oetafia; Devi Ratnasari; Budi Purwoko (Jurnal Ilmiah Global Education, 2026)
This study aims to determine the dominant conflict resolution style used by students with authoritarian parenting styles, as well as to determine the impact of students' psychological well-being on conflict resolution styles arising from authoritarian parenting styles. This study uses the five conflict resolution styles theory proposed by Thomas and Kilmann to determine the dominant conflict resolution style used, as well as the seven aspects of psychological well-being theory proposed by Carol Ryff as aspects to measure the impact of students' psychological well-being. The respondents in this study were selected using purposive sampling with the criteria of students who were raised with an authoritarian parenting style and still live with their parents. This study used a qualitative case study approach with data collection techniques in the form of semi-structured interviews with four students who experienced authoritarian parenting. The data analysis used in this study was the Miles and Huberman model through three main processes, namely data reduction, data presentation, and conclusion drawing. The results of the study found that this parenting style resulted in the formation of avoiding and accommodating conflict resolution styles among students. This had an impact on the psychological well-being of students. The six aspects of psychological well-being identified by Ryff show a tendency that psychological well-being has not developed optimally, especially in the aspects of self-acceptance, positive relationships with others, autonomy, life purpose, and personal growth. This has an impact on students' psychological well-being. The six aspects of psychological well-being identified by Ryff show a tendency for psychological well-being to be underdeveloped, particularly in terms of self-acceptance, positive relationships with others, autonomy, lpurpose in life, and personal growth.